An Analysis of the Current International Legal Regime on the Protection of the Cultural Heritage of Indigenous Peoples - Belyaeva, Galina S.; Komnatnaya, Yulia A.; Mohammed, Sanka; Safronova, Elena V.; Samsonov, Valeriy N. (Journal of History Culture and Art Research, 2017)
Indigenous peoples have always strived for recognition of the right to their ancestral lands, resources, protection of their language, customs and traditions, all of which in combination constitute their (cultural) identity. This strife for recognition of their cultural rights, even if misinterpreted by some, is justifiable given that indigenous peoples’ very survival depend on their cultural ties to lands, customs, traditions etc., passed down from generation to generation. Departing from initial attempts at integrating indigenous peoples into the rest of the society, the current legal regime recognizes distinct cultural rights of indigenous peoples. However, the absence of explicit references to indigenous peoples’ right to their own cultural heritage in the relevant human rights instruments casts an uncertainty over the possibility that the cultural rights of indigenous peoples include a right to their cultural heritage over which they will exercise control. This article studies the current situation regarding indigenous cultural heritage right claims and elaborates on the various hurdles preventing the realization of this right. Addressing the uncertainties surrounding the existence of indigenous peoples’ right to their own cultural heritage, international treaty law, customary international law and case law are analyzed to make a proposition that there is, indeed, evidence of such a right under international law. Conceding the lack of clarity on this issue, recommendations towards a more effective regime on the protection of cultural heritage rights of indigenous peoples are suggested.